Reactivity of difunctional polar monomers and ethylene copolymerization: a comprehensive account - Gaikwad, Shahaji R.; Deshmukh, Satej S.; Koshti, Vijay S.; Poddar, Suparna; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Chikkali, Samir H. (Macromolecules, 2017)
A comprehensive picture of insertion of 1,1-disubstituted difunctional olefins, their ability to double the functional group density at the same level of incorporation as that of monofunctional olefin, and copolymerization with ethylene has been demonstrated. Exposure of a palladium complex [P boolean AND OPdMe(L)] (P boolean AND O = kappa(2)-P,O-Ar2PC6H4SO2O with Ar = 2-MeOC6H4.; L = C2H6OS) to methyl 2-acetamidoacrylate (MAAA) revealed slight preference for 1,2-insertion over 2,1-insertion (1.0:0.7). In contrast, insertion of electron-deficient 2-(trifluoromethyl)acrylic acid (TFMAA) unveiled selective 2,1-insertion {via [(P boolean AND O)PdC5H6F3O2] (11)1. The unstable intermediate 11 undergoes beta-hydride and beta-fluoride elimination to produce subsequent insertion and elimination products. The identity of elimination products (E/Z)-2-trifluoromethyl)but-2-enoic acid [17(E/Z)] and 2-(difluoromethylene)butanoic acid (13) was fully established by 1-2D NMR spectroscopy. These insertion experiments, taken together with insertion rates, suggest that MAAA and TFMAA. are amenable to insertion. Polymerization of ethylene with MAAA, TFMAA, acetamidoacrylic acid, 2-bromoacrylic acid, dimethyl allylmalonate, and allylmalonic acid was catalyzed by [P boolean AND OPdMe(L)] (L = C2H3N) (S.ACN), and the highest incorporation of 11.8% was observed for dimethyl allylmalonate (DMAM). The changes in the surface properties of the copolymers after incorporation of difunctional olefins were evaluated by measuring the water contact angle. Copolymer with highest (11.8% of DMAM) incorporation revealed a reduced water contact angle of 76 degrees. These findings demonstrate that 1,1-disubstituted difunctional olefins are amenable to polymerization, and incorporation of difunctional olefins In polyethylene backbone leads to the production of relatively hydrophilic polyethylene copolymers.

Renewing polyethylene: insertion copolymerization of sugar derived hydrophilic monomers with ethylene - Rajput, Bhausaheb S.; Pawal, Sandip B.; Bodkhe, V. Dnyaneshwar; Rao, I. Nagamalleswara; Sainath, Annadanam V. Sesha; Chikkali, Samir H. (European Polymer Journal, 2020)
Although highly desirable, insertion copolymerization of renewable resource derived functional olefins with ethylene has been rarely investigated. Herein, we report insertion copolymerization of challenging sugar derived isohexide mono-enes with ethylene in the presence of Pd-phosphinesulfonate acetonitrile catalyst (C1). Thus, copolymerization of ethylene with isomannide mono-ene (2a), isosorbide mono-ene (2b'), isoidide mono-ene (2c) and methacryl-2,3,4,6-tetra-O-acetyl-D glucopyranoside (2d) afforded corresponding functionalized polyethylene (P2a-1 to P2d-1). High temperature proton NMR investigations revealed enchainment of 2a-2c in polyethylene backbone and the highest incorporation of 1.45% was observed for 2c. The high temperature proton NMR results were further corroborated by solid state C-13 NMR and IR spectroscopy. Gel permeation chromatography analysis displayed weight average molecular weight in the range of 13.0-27.2 x 10(3) g/mol. The thus prepared copolymers revealed melting temperature in the range of 117-126 degrees C. Relatively reduced melting temperature compared to neat polyethylene may suggest an irregular arrangement of pendant functional group on polyethylene main chain.
Keywords: Hydrophilic polyethylene; insertion copolymerization; Isohexide mono-enes; Polyethylene; Sugar

Refining plant oils and sugars to platform chemicals, monomers, and polymers - Pandey, Swechchha; Rajput, Bhausaheb S.; Chikkali, Samir H. (Green Chemistry, 2021)
As fossil resources continue to dwindle and environmental concerns are magnified, finding sustainable alternatives is the only way to mitigate resource availability and derisk the planet. The principles of Green Chemistry may provide guidance in this case, and renewable resources can be converted into useful platform chemicals, monomers, and polymers. This critical review examines the possibility of utilizing renewable plant oils and sugars to produce feedstock chemicals, monomers, and polymers. Among the seven isomerizing functionalization reactions of plant oils, isomerizing alkoxycarbonylation displays the highest terminal selectivity. Despite the low reactivity of sugar-derived isohexides, new strategies have been deployed to convert isohexides into difunctional monomers and polymers. The commercialization of isohexides and a few polymers derived from these building blocks has just commenced. Thus, challenges associated with isomerizing functionalization of plant oils and the use of sugar-derived isohexides in chemical syntheses have been summarized, and the potential of these renewable resources has been evaluated.

Rh-catalyzed asymmetric hydroformylation of olefins using phosphorus ligands - Kumar, Rohit; Sen, Anirban; Chikkali, Samir H. (Journal of chemical sciences, 2023)
Easily accessible BINOL-based monodentate phosphite ligand L1 and hybrid ligand L2 have been synthesized in good yield by following a one-pot, two-step protocol. A single 31P resonance at 146.6 ppm confirmed the formation of L1. Subsequent 1-2D NMR and mass spectrometric analysis authenticated the existence of L1. These ligands afforded excellent activity and regio-selectivity in the Rh-catalyzed AHF of styrenic substrates. L1 showed excellent regioselectivity but did not discriminate between the two enantiomers, while L2 displayed an enantiomeric excess (ee) of up to 20%. In our attempts to understand the reasons for low ee, the coordination behavior of L2 was investigated. The coordination study revealed that L2 coordinates with the Rh as a monodentate ligand, although there are two P-sites. It was found that only the phosphine arm was coordinated to the Rh and the phosphite arm stayed away from the Rh core at the ambient temperature, leading to moderate ee.Graphical abstractOne-step synthesis of a phosphite (L1) and a phosphine-phosphite (L2) ligand and their implication in the asymmetric hydroformylation of olefins with excellent regioselectivity (>95%) and moderate enantioselectivity (up to 20%) is reported.
Keywords: catalysis; coordination; Hydroformylation; Phosphine-phosphite ligand; Phosphite ligand

Regulating the polyethylene microstructure by increasing steric crowding in naphthoxy imine-ligated Ni(II) complexes - Birajdar, Rajkumar S.; Gonnade, Rajesh G.; Chikkali, Samir H. (Polymer Chemistry, 2024)
Ligands play a prominent role in ethylene polymerization. However, it is a highly challenging task to regulate branching through ligand modifications. Here we report the synthesis of systematically sterically tailored naphthoxy imine-ligated nickel complexes (Ni1, Ni2, and Ni3), their performance in ethylene polymerization, and how the ligand steric controls branching in the resultant PE. Ni1-Ni3 were prepared in one step with an excellent yield (73-93%). The identity of these complexes was unambiguously ascertained using H-1, C-13, 2D NMR spectroscopy, mass analysis, and single-crystal X-ray diffraction. The molecular structure revealed a cis arrangement of alkyl/aryl and donor groups (C-Ni-D), which is necessary for initiating ethylene polymerization. Buried volume contours suggested Ni3 to be sterically the most bulky among the three. When exposed to ethylene, the three nickel complexes Ni1, Ni2, and Ni3 produced polyethylene with excellent activity. As predicted by buried volume calculations, dibenzhydryl-substituted Ni3 outperformed sterically less crowded Ni1 and Ni2. Careful analysis of the resultant PE disclosed that sterically less encumbered Ni1 and Ni2 produce PE with high branching (43-54 branches/1000-C atoms) density. However, the bulkiest Ni3 revealed much lower branching (28 branches/1000-C atoms) and a high TOF of 35 400 mol of PE per mol of Ni per h, along with a high molecular weight of PE (61 000 Da). The steric bulk in Ni3, most likely, reduces chain-walking and thus lowers branching in the resultant PE. As compared to the literature-reported analogous Pd1 catalyst, the Ni3 catalyst discloses high TOF, high molecular weight, and less branched, linear polyethylene.
Keywords: Catalyzed Olefin Polymerization; High-Temperature; Molecular Weight

Renewable and degradable polyoxalates derived from castor oil - Menon, Abhijith Hari; Joseph, Seena; Shaikh, Maulali H.; Chikkali, Samir H. (Macromolecular Chemistry and Physics, 2025)
Renewable feedstocks pave the way to reduce the demand for petroleum-derived chemicals. Castor oil is one such plant-based raw material that can be used to synthesize chemicals and materials with diverse applications. Herein, we report the synthesis of a novel monomer, 18-methoxy-18-oxooctadec-9-en-7-yl methyl oxalate (3), from castor oil-derived ricinoleic acid. The identity of the monomer 3 has been unambiguously ascertained using 1-2D NMR spectroscopic analysis. Monomer 3 was then subjected to condensation polymerization with potentially bio-renewable long-chain aliphatic diols to yield degradable linear polyoxalates having molecular weights in the range of 8000-22,000 g/mol. The polymerization reactions were performed using pTSA and [Sn(Oct)2] as catalysts, and the polymerization conditions were optimized. The structure of the polymer was confirmed by 1-2D NMR spectroscopy, IR spectroscopy, and GPC analysis. The thermal characterizations of the polyoxalates were carried out by DSC and TGA analysis. The polyoxalates were found to degrade in acidic media. These renewable polyoxalates were further reacted with thiols by ``thiol-ene'' click reaction to produce a cross-linked rubbery polymer, which retained degradability.
Keywords: castor oil derivatives; hydrolytic degradations; polyoxalates

Rh-Catalyzed Asymmetric Hydroformylation: The Case of Substituted and Heterocyclic Olefins - Tewari, Tanuja; Khopade, Kishor V.; Chikkali, Samir H. (ChemCatChem, 2025)
Asymmetric hydroformylation (AHF) of prochiral alkenes is an efficient way to synthesize optically active aldehydes, which are versatile chiral building blocks for pharmaceuticals, agrochemicals, and other fine chemicals. The purpose of this review is to take stock of developments in the last decade and shed light on the understanding of the field of AHF. So far, most of the literature methods focused on the use of Rh-based catalysts, due to high catalytic activity and excellent chemoselectivity for the aldehydes. Several chiral phosphorus ligands have been successfully developed for Rh-catalyzed AHF reactions. This review examines the role of the substrate/olefins in AHF. Several different types of ``mono-substituted'' terminal olefins (functionalized/nonfunctionalized) with a variety of chiral ligands have been investigated, which show high activity and excellent ee of up to 99%. The AHF of ``di-substituted'' and ``tri-substituted'' olefins is rarely reported. This review summarizes the evolution of chiral ligands for AHF. It discusses the progress made in desymmetrizing hydroformylation. In addition, it highlights important developments in AHF carried out with and without syngas. These advances span a wide variety of alkenes. Additionally, the review offers future approaches in the field of AHF for the synthesis of optically active aldehydes.
Keywords: Asymmetric hydroformylation; Asymmetric transfer hydroformylation; Chiral ligands; Desymmetrizing hydroformylation; Substituted alkenes

Ruthenium-catalyzed deconstruction of polyolefins: a strategy to up-cycle waste polyethylene to value-added alkene - Padhi, Ganeshdev; Khopade, Kishor V.; Moyilla, Nageswararao; Rangappa, Raghavendrakumar; Chikkali, Samir H.; Barsu, Nagaraju (Angewandte Chemie-International Edition, 2025)
Synthesis of value-added products from post-consumer waste polyolefins is fascinating as well as challenging. Here we report ruthenium-catalyzed up-cycling of the polyethylene to long-chain alkene derivatives. The developed methodology mainly involves two steps i.e., dehydrogenation of polyethylene through hydrogen atom transfer and its metathesis using the HG-II catalyst. The dehydrogenation of polyethylene using ruthenium catalysis derived up to 3.38 %, of double bonds; with 90 % of the recovered polyolefin material. The obtained unsaturated polyethylene was subjected to cross-metathesis with ethylene using HG-II catalytic system. This resulted in the synthesis of predominantly dodecene (C12) derivatives, with 58 % selectivity, along with other derivatives of varying chain lengths. The overall reaction produced terminal and internal olefins in the ratio 1:0.8 respectively. The dehydrogenation of polyethylene and its deconstruction was confirmed by NMR spectroscopy, Gel Permeation Chromatography (GPC) and Differential Scanning Calorimetry (DSC). The origin of C12 selectivity has been demonstrated by control experiments. The scope of the methodology was extended to post-consumer waste polyethylene which gave high conversion to value-added dodecene derivatives as a major product.
Keywords: Deconstruction; Homogeneous catalysis; ruthenium; Upcycling; Waste plastic